Reproductive diseases and disorders of dairy cows in the Gazipur district (Bangladesh Journal of Agriculture, 2022)
Reproductive diseases and disorders of dairy cows significantly reduce their productivity which is of great concern to dairy producers because most reproductive disorders adversely affect future fertility. The objective of this study was to determine the incidence of reproductive diseases and disorders in dairy cows at Gazipur Sadar Upazila of Bangladesh. A total of 2430 dairy cows from total 150 small (10 dairy cows) dairy farms were studied using predesigned questionnaires during January 2016 to December 2018. Twenty reproductive diseases and disorders were diagnosed. Among them, the major reproductive diseases and disorders were anestrous, mastitis, repeat breeding, metritis, retained placenta, and the minor problems were heat detection diseases and disorders. Total incidence of reproductive diseases and disorders was 21.51%, among the major reproductive diseases and disorders, incidence of anoestrus 6.79%, mastitis 3.66%, repeat breeding 3.20%, metritis 2.34%, retained placenta 1.31% and heat detection 1.06%. The highest occurrence of reproductive disease was anoestrus in dairy cows with low body condition score (BCS ≤ 2) than that with fair (2.5) and good (≥3-3.5) body condition scores. Anoestrus, mastitis, and repeat breeder should get top priority considering reproductive diseases and disorders research to gain more knowledge to control them in the study area context.Bangladesh J. Agri. 2022, 47(1): 95-101